Morphological Characteristics of the Stomach of the Swamp Buffalo (Bubalus bubalis) - Anni Nurliani; Teguh Budipitojo; Dwi Liiek Kusindarta (Aceh International Journal of Science and Technology, 2015)
The ability of swamp buffaloes for adaptation to swampland was suggested to be supported by their digestive system efficiency including absorption one. This research was done to obtain scientific explanation about digestive efficiency of swamp buffalo by investigating swamp buffalo stomach morphologically. Six stomachs were obtained at slaughterhouse from 2.5-3 years old healthy male swamp buffaloes. Every part of the stomach includes nonglanduler stomach (forestomach: rumen, reticulum, and omasum) and glanduler stomach (abomasum) was taken for measuring length, width, and weight organs. Then all of samples from each part of stomach were prepared for morphological observation. The data were analyzed descriptively. Stomach of swamp buffalo had morphological peculiarities, such as: mucosa surface of rumen, reticulum, and omasum has black color, and there is variation of ruminal papillae of swamp buffalo, including branching. Special characteristics of swamp buffalo stomach is estimated as supporting morphological factors for increasing digestive efficiency to survive in swampland.